Influence of tillage, cultivar, seed rate and planting geometry on wheat yield - Chhokar, Rajender Singh; Sharma, Ramesh Kumar; Gill, Subhash Chander; Kumar, Raj (Journal of Cereal Research, 2017)
Field investigations were conducted to improve the wheat yield through adjustments in seed rate, spacing, and sowing method at Indian Institute of Wheat and Barley Research, Karnal, Haryana during rabi seasons of 2008-09 to 2012-13. The results showed that by using the precision seed drilling, seed rate from present recommendations of 100 kg can be reduced to 75 kg/ha, however further reduction in seed rate caused the yield reductions. If we translate 25% saving across the wheat growing area of India (30 mha) then we can have a huge saving of about 7.5 x 106 q/year. The yield improved as the spacing reduced from 22.5 to 15 cm although yield was not significantly different among 15, 17.5 and 20 cm spacing. Among three varieties (PBW 550, PBW 502 and DBW 17) maximum yield was produced by PBW 550. Among three crop establishment methods viz. no till (NT), conventional till (CT) and bed planted wheat, the lowest yield was obtained in bed planted system, whereas the NT and CT had similar yield levels. In 2 and 3 rows bed planted system, 3 rows on bed planted system yielded more compared to 2 rows system. Yield improved with bidirectional (criss-cross) sowing (Â½ + Â½ seed) compared to uni-directional sowing. The results of the present studies clearly indicate that wheat yield can be improved through right choice of cultivar, seed rate, spacing and crop establishment methods (Criss- cross sowing).DOI:10.25174/2249-4065/2017/71641